Tuñón de Lara, los historiadores contemporáneos y la transición democrática - Forcadell, Carlos (Cuadernos de Historia Contemporánea, 2009)
This article reviews the work and historiographical evolution of Manuel Tuñón Lara in the context of the last third of the twentieth century. The publication of El movimiento obrero en la Historia de España is a momentous occasion for the labour movement’s history. The second part analyses the role of Tuñón de Lara in the transition to modern historiography in Spain.
Keywords: Manuel Tuñón de Lara; Labour movement; Social history; Historiography; Transition to democracy